Performance of Sugarcane Farming Ratoon System in East Java Province - Arief Joko Saputro; Nuhfil Hanani; Fahriyah Fahriyah (HABITAT, 2021)
The fulfillment of national sugar consumption needs cannot be achieved by domestic production. Increase sugar cane production to fulfill the availability of sugar in Indonesia, one of which in the central production area of East Java is still constrained by many sugarcane farmers who are doing ratoon system more than three times, so the productivity is low. This study aimed to analyze the performance sugarcane farming ratoon system in East Java by looking at technical efficiency and scale efficiency using the non-parametric approach of Data Envelopment Analysis (DEA). Sampling in this study used multistage random sampling in Kediri, Malang, and Mojokerto Districts. The average total technical efficiency (TE CRS) of farmers with 1-3 ratoons is 0.754, the pure technical efficiency (TE VRS) is 0.817, and the scale efficiency is 0.926. The average TE CRS of farmers with 4-6 ratoons is 0.693, TE VRS is 0.814, and the scale efficiency is 0.860. For farmers who do more than seven ratoons, an average TE CRS is 0.609, TE VRS is 0.693, and scale efficiency is 0.894. The majority of sugarcane farmers at the research site have not been on an optimal business scale, namely in IRS conditions.